Pengembangan Instrumen Penilaian Supervisi Manajerial Kepala Sekolah PAUD Berbasis Website - Dian Widi Yussanti; Yari Dwikurnaningsih (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to develop website-based managerial supervision assessment instruments to help the duties of kindergarten supervisors in carrying out supervision managerial. This type of research refers to the Borg and Gall R&D model, modified by Sugiyono. The development research covers potentials and problems, data collection, product design, design validation, design revision, product trials, product revisions. The result of this research is Website-Based Managerial Supervision of School Principal Supervision Assessment Instrument or InPeSiM, guidelines for using InPeSiM for Supervisors and Principals. Based on the results of expert validation, InPeSiM was declared to be very complete and worth testing. Whereas in the field trial, Supervisor stated that the product was very good to used in managerial supervision.